Changes in bacterial and archaeal communities in anaerobic digesters treating different organic wastes. (December 2015) - Kim, Young Mo; Jang, Hyun Min; Lee, Kwanyong; Chantrasakdakul, Phrompol; Kim, Daegi; Park, Ki Young
Highlights: BMP tests were conducted using representative organic wastes. Biomethanation of food wastes produced a high yield of methane. Bacterial communities distinctly shifted in the presence of different organic wastes. The dominance of the main methanogens slightly shifted in between the different ADs. Abstract: The goal of this study was to characterize microbial communities in anaerobic batch digesters treating different representative organic sources (sewage sludge, food waste, septage). Among the digesters, the anaerobic digester of food waste had the highest methanogen density, producing a peak value methane yield of 813.2 mL CH4 /g VS. In all the digesters, acetoclastic Methanosarcinales and hydrogenotrophic Methanomicrobiales were the most dominant methanogen groups, but their proportion among the methanogens varied depending on the organic sources. The bacteria community in the anaerobic digestion (AD) of food waste and septage was distinctly different from that found in the AD of sewage sludge (primary sludge and waste activated sludge). Shifts in both bacterial and archaeal community structures could be related to differences in chemical properties, production, and accumulation of intermediates digested from organic wastes having different characteristics. These findings could prove useful in optimizing the microbial community to enhance AD process treating organic wastes.